"Do your internal branding efforts measure up?": Consumers' response to brand supporting behaviors of hospitality employees. Issue 5 (13th July 2015) - Erkmen, Ezgi; Hancer, Murat
Abstract : Purpose: – This study aims to understand the effect of brand citizenship behaviors of hospitality employees on customers' relation with the brand. A model, which links employee behaviors to customers' evaluation of brand performance, brand trust and brand commitment, is proposed to provide further insight into how customers form their relation with a brand. Design/methodology/approach: – Data were collected from both customer-contact employees and passengers of a corporate airline company. Structural equation modeling was used to test the proposed model by using both employee and customer data in the same research model. Findings: – The results showed that even brand citizenship behaviors of employees did not affect brand commitment of customers directly; these behaviors explain customers' commitment to a brand through influencing perceived brand performance of customers and their trust toward a brand. Overall, this study provided support for the impact of employees' brand-related behaviors on consumers' relation with the brand. Research limitations/implications: – The results suggest that hospitality employees contribute to the brand success through their behaviors. This helps organizations to enhance brand-related behaviors of their employees to ensure long-term relationships not only with customers but also with their employees in a labor-intensive and high customer contact industry. Originality/value: – This research was one of the first to analyze the effects of employees' brand supporting behaviors on consumers by using both employee and consumer data in the same research model within the hospitality context.